2021
DOI: 10.1136/bmjopen-2020-043544
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microfinance health interventions on health-related outcomes among female informal workers in Pakistan: a retrospective quasi-experimental study

Abstract: ObjectiveThe purpose of this study is to assess the impact of microfinance health interventions (health insurance and health-awareness programmes) on health-related outcomes among female informal workers in Pakistan.DesignWe conducted a retrospective, quasi-experimental study among a total of 442 female borrowers from seven microfinance providers (MFPs) across four provinces of Pakistan in 2018. A standardised tool was used for data collection. Probit regression was used to identify the probability of female b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Three studies reported significant improvements in some of the outcome measures assessed [ 21 , 23 , 25 ]. Two studies assessed only one outcome measure and one reported a positive improvement while the other reported no significant effect [ 22 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported significant improvements in some of the outcome measures assessed [ 21 , 23 , 25 ]. Two studies assessed only one outcome measure and one reported a positive improvement while the other reported no significant effect [ 22 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study evaluated overall patient satisfaction and reported a positive association (Supplementary Appendix S4) [19]. Five studies assessed self-reported health outcomes (Supplementary Appendix S4) [21][22][23][24][25]. Three studies reported significant improvements in some of the outcome measures assessed [21,23,25].…”
Section: Outcome Dimensionmentioning
confidence: 99%
“…High empowerment contributed to enhancements in the usage of contraceptives and mental health as well as decreases in the risk of intimate partner violence [33]. When women were borrowing in groups and attending regular meetings at microfinance banks, their chances of having better health outcomes increased [34]. The various child nutrition indicators were higher who received microfinance services compared to the control group [35].…”
Section: Impact Of Microfinance Intervention On Health Statusmentioning
confidence: 99%
“…The affordability of fresh fruits and vegetables in the neighborhood also affects the health of the mother, child, and the entire family [17]. Disadvantaged communities which have better access to loans [19] and insurance schemes [20] are known to have better outcomes for maternal and child health.…”
Section: Introductionmentioning
confidence: 99%